Analysis of the demonstration of the Indonesian house of representatives' allowances in 2025 - Hutapea, Inggrid Brigita Vinsensa; Situmorang, Beatrice Oktaviana; Widayat, Benedicta Karen Jasmine; Gayatri, Kiska Alexandra; Levinawati, Tatiana Wuryadi (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This article examines the gap between political elites and public aspirations within Indonesia’s multiparty presidential system. The focus of the study is on the response of the government and the House of Representatives to the demonstrations against the 2025 House of Representatives allowance. Methods: The research utilizes a qualitative descriptive-analytical approach, synthesizing data from legislation, academic literature, and national media reports through thematic analysis to reconstruct the state's response to public pressure. Data validity is ensured through library research and triangulation of official state documents with long-term media reports, analyzed through thematic coding to identify patterns between shifts in state policy and public legitimacy. Findings: The findings of this study confirm that political participation is not only realized through elections, but also through collective action by the community in demanding accountability and social justice. The 2025 protests demonstrated that massive public pressure can force a policy shift, as evidenced by the cancellation of state agendas and the opening of dialogue, yet it also revealed the state’s tendency to respond only when public unrest reaches a crisis level. Conclusion: The 2025 demonstrations show that political legitimacy is highly dependent on the state's sensitivity to public aspirations. In addition, the role of digital space as a new arena for political discourse contestation also influences the escalation of conflict and the formation of public opinion. Therefore, sustainable democracy requires the state's ability to listen to, respond to, and substantively integrate the voices of the people in the policy-making process. Novelty/Originality of this article: The novelty of this research lies in its critical examination of